2013
DOI: 10.1556/eujmi.3.2013.4.6
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity of some medicinal plants against selected human pathogenic bacteria

Abstract: Medicinal plants are traditionally used for the treatment of human infections. The present study was undertaken to investigate Bergenia ciliata, Jasminum officinale, and Santalum album for their potential activity against human bacterial pathogens.B. ciliata, J. officinale, and S. album extracts were prepared in cold and hot water. The activity of plant extracts and selected antibiotics was evaluated against five bacterial pathogens including Staphylococcus aureus, Bacillus subtilis, Proteus vulgaris, Pseudomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 10 publications
5
44
0
5
Order By: Relevance
“…Several authors have reported on the antimicrobial effects of J. officinale, C. sinensis and C. limon EO in vitro. Khan et al [18] observed antimicrobial activity of the cold water extract of J. officinale (leaves) against Pseudomonas aeruginosa followed by Bacillus subtilis, Escherichia coli and Proteus vulgaris. Viuda-Martos et al [19] have found that orange essential oil was the most effective against A.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Several authors have reported on the antimicrobial effects of J. officinale, C. sinensis and C. limon EO in vitro. Khan et al [18] observed antimicrobial activity of the cold water extract of J. officinale (leaves) against Pseudomonas aeruginosa followed by Bacillus subtilis, Escherichia coli and Proteus vulgaris. Viuda-Martos et al [19] have found that orange essential oil was the most effective against A.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Linaceae Linum usitatissimum L./ Morgah biodiversity park, Rawalpindi, Pakissstan Agar well diffusion method [113] 10 0 15 6.5 Agar well diffusion assay [120] 25 10.5 [25,125] Methanol 10 n-Butyl alcohol 15 Anti-pneumonial and anti-tuberculosis plants Muhammad Adnan et al Agar well diffusion method [21,43,126] Pelargonidin-3-galactose 18 Agar well diffusion method [58] Hot Water 13 Ceftriaxone 20 A pinch of salt is added to make tea. One cup of tea is taken at bedtime for 10-15 days/Pneumonia N/A Agar disc well diffusion method [133,134] Umbelliferae [71,139] 0.15 10 Anti-pneumonial and anti-tuberculosis plants Muhammad Adnan et al Agar well diffusion methods [143] Petroleum ether Staphylococcus aureus (ATCC 6571) 50 19…”
Section: 9mentioning
confidence: 99%
“…However, the mechanisms of their actions and their efficacy, in general, are not fully studied. [2].…”
Section: Introductionmentioning
confidence: 99%